MENGEKSPLENASI KARYA MULYANA MOGUS - Sarah, Yuni (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
Mulyana Mogus is one of the artists who is known for his fiber art with knitting techniques and also the concept of his work which has a witty character that is obtained in his daily life is quite thick attached to his work. The advantages in creative thinking and the elements contained in Moel's work are the authors try to analyze his work from expertise, material and medium, as well as the expressions contained in his work. This research is intended to understand the meaning of the aspects contained in the work. This research method uses a qualitative method by using the analysis of the elements of art. Mulyana's fiber art works are works that highlight mysterious underwater phenomena, no wonder his works present marine life and marine animals such as coral reefs, octopuses, fish and other creatures. His works are packed with bright colors and attractive shapes. Mulyana is able to present a narrative full of attractions on each strand of yarn that is knitted and also presents various layers of dimensions and Mulyana's expertise in processing harmonious bright colors. Mulyana makes the original texture of knitted yarn resembles the original texture of the object displayed through the single crochet technique. Starting from the density of the yarn, to the type of yarn used is chosen to produce different textures Based on the discussion, the art that produced not only to be enjoyed alone and the artist must also have the expertise to combine the elements of visual art in process of producing an art works. Pay attention to the material in order to be able to master the medium used. Content and content cannot be separated from the embodiment of the work, then the idea of ​​​​the form of the work is realized as expressively as possible in the medium without forgetting the subject meter, in Mulyana's work he manages to master all visual elements from the shape of color to texture to produce works that educate the public who see the content raised.